Wilfred Ethier. Modern International Economics. New York: W. W. Norton and Company. 1983. xviii + 588 pp. (The Pakistan Development Review, 1988)
Its been long recognized that various economies of the world are interlinked through international trade. The experience of the past several years, however, has demonstrated that this economic interdependence is far greater than was previously realized. In this context, the importance of international economic theory as an area distinct from general economics hardly needs any mentioning. What gives international economic theory this distinction is international markets for some goods and effects of national sovereignty on the character of economic activity. Wilfred Ethier's book, which incorporates recent developments in the field, is an excellent addition to textbooks on international economics for one- or twosemester undergraduate courses. The book mostly covers standard topics. A distinguishing feature of this book is its detailed analysis of the flexible exchange rates and a discussion of the various approaches used for their determination. Within each chapter, the author has extensively used facts, figures and major events to clarify the concepts in the light of the theoretical framework. The book also discusses, in a fair amount of detail, the existing international monetary system and the role of various international organizations.